Phase-Field Model of Hydride Blister Growth Kinetics on Zirconium Surface - Wu, Shuai; Sheng, Jie; Yang, Chao; Shi, Xiaoming; Huang, Houbing; Liu, Yu; Song, Haifeng (Frontiers in Materials, 2022)
The precipitation of zirconium hydride blisters on the surface of zirconium alloy cladding destroys the integrity of the material and leads to material failure, which has serious potential safety hazards. To study the corrosion kinetics of zirconium hydride blisters, we established a phase-field model coupled with anisotropic elastic, which can reflect the microstructure evolution process of zirconium hydride blisters. The model studies the natural growth of hydride blister and the structural evolution process after applying radial stress and discusses the corrosion characteristics, stress distribution, and displacement changes. Zirconium hydride blisters tend to be semi-ellipsoidal in natural growth. Applying radial outward stress will promote the growth of blisters and aggravate the harm of corrosion. The stress state changes with applying stress, which affects the elastic driving force, resulting in the change of blister morphology. This work is helpful to understand the corrosion kinetic mechanism of hydride blisters.